Metode Activity Based Costing Dalam Menentukan Harga Pokok Produksi Mousse Cake Pada Toko Kue IST Patisserie Medan - Alhabsy, Natasha (Cattleya Darmaya Fortuna, 2022)
The activity based costing approach is a straightforward method of computation that bases the price of a good or service on the idea that the activity itself generates the cost rather than the product or service that uses it. The goal of this study was to compare the cost of production utilizing the Activity Based Costing method with the method currently employed by Toko Kue IST Patisserie Medan. The analysis approach that is being employed is descriptive quantitative. The results showed that the determination of cost of good manufactured (HPP) using ABC gives more accurate results than the usual techniques in Pastry Shop IST Patisserie Medan. Mousse Cake Chocolate and Mousse Cake mousse Cake Coffee products experience overcosting or excess cost of Rp. 8.954, while Mango Mousse Cake overcosting Rp. 35.143.